Morfologi dan variasi morfometrik stingless bees di Kepulauan Maluku, Indonesia - Yofian Anaktototy; Windra Priawandiputra; Tiara Sayusti; Jacobus SA Lamerkabel; Rika Raffiudin (Perhimpunan Entomologi Indonesia, 2021)
Stingless bees are widely distributed in tropical regions including Indonesia, and currently three species of stingless bee have been recorded in the Moluccas. The aims of this study were to explore the species and distribution of stingless bees in the five islands in the Moluccas (Seram, Ambon, Haruku, Saparua, and Nusalaut island) and compare the morphometric variations of stingless bees within and among islands. The samples of stingless bees were identified based on twelve morphological characters, resulting in two species of Tetragonula fuscobalteata (Cameron) and T. sapiens. (Cockerell). T. fuscobalteata found to be a new record in the Moluccas, and showed significantly lower morphometric parameters compared to those of T. sapiens (P < 0.001). Based on non-metric multidimensional scaling (NMDS) analysis, the combination of twelve morphometric parameters between T. fuscobalteata and T. sapiens were significantly different. Almost all morphometric parameters of T. fuscobalteata showed highly varied among islands, except the width of gena of this stingless bees. T. fuscobalteata from Ambon, Haruku, Saparua, and Nusalaut were mostly clustered based on NMDS analysis, while those from Seram show high variations. This study found T. sapiens in three different islands, Seram, Ambon, and Haruku. Width of thorax, mesonotum, and propodeum length of T. sapiens were significantly different among these three islands (P < 0.001). This study has contributed to the new distribution data of T. fuscobalteata and T. sapiens in the Moluccas and showed variation of morphometric parameters of the two stingless bee species among islands in the Moluccas.